Pelatihan Penggunaan Media Digital dalam Pembuatan Karangan Bahasa Jepang untuk Tingkat Dasar - Alifah, Rahma Fitri; Roosiani, Indun; Saptaji, Hargo (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
The purpose of the community empowerment activity with the theme "Strategi Pengajaran Sakubun Tingkat Dasar" is to provide knowledge and understanding to Japanese language teachers, especially at the senior high school level or its equivalent, on how to use digital media to teach sakubun. This activity was conducted through a two-day webinar (on October 23, 2023, and February 24, 2024) using the zoom meeting platform. Participants in this Community Empowerment webinar gained insights into effective ways digital media can be used to support classroom teaching, particularly in writing Japanese compositions, or sakubun. The goal of this webinar was not only to provide knowledge to Japanese language teachers but also to address common challenges in teaching sakubun, which is a demanding learning activity that requires considerable time and effort to give students meaningful feedback. By participating in this webinar, it is hoped that these challenges can be reduced, ultimately benefiting learners of the Japanese language.